2001
DOI: 10.1016/s0165-1765(00)00329-3
|View full text |Cite
|
Sign up to set email alerts
|

Group size and free riding when private and public goods are gross substitutes

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Users clearly have an incentive to free ride with respect to content and bandwidth, which means "taking their share of it and keeping their own resources for themselves" (Marwell and Ames 1979). Economic literature on private provision of public goods suggests that typically the free riding problem worsens with the group size (see, for example, Isaac and Walker 1988;Gaube 2001). Asvanund et al (2002) confirmed the existence of a positive correlation between free loading and crowding in P2P networks.…”
Section: Resource Sharingmentioning
confidence: 90%
“…Users clearly have an incentive to free ride with respect to content and bandwidth, which means "taking their share of it and keeping their own resources for themselves" (Marwell and Ames 1979). Economic literature on private provision of public goods suggests that typically the free riding problem worsens with the group size (see, for example, Isaac and Walker 1988;Gaube 2001). Asvanund et al (2002) confirmed the existence of a positive correlation between free loading and crowding in P2P networks.…”
Section: Resource Sharingmentioning
confidence: 90%
“…Following the analysis in Gaube (2001), I will employ the Lindahl allocation as a reference point for efficient charitable giving. 10 In the present context, the Lindahl equilibrium is defined as follows:…”
Section: The Modelmentioning
confidence: 99%
“…Gaube (2001) has pointed out that the additional assumption of gross substitutability between these commodities is sufficient for a negative effect of group size on the variable (iii).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations